Extrapolation of Fandorin character in the European history: “The Falcon and the Sswallow” by B. Akunin (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article analyzes the extrapolation of the figure of Erast Petrovych Fandorin, the hero of many novels, stories, short stories by Boris Akunin, into the European history. For this, the author considers the novel «Falcon and Swallow», in which characters are presented by his grandson Nicholas and his ancestors, in particular Letitia von Dorn. Events take place in two time periods, in 1702 and 2009. “Falcon and Swallow” by B. Akunin as well as a number of his other novels, contribute to give out the quasibiography of Fandorin as the biography of the real person who lived and worked in the context of real historical events of that time. Erast Petrovych himself personally does not appear in the work. But we have his distant ancestors and descendants, who are components of the chain in the generic tree of the hero created by the imagination of the author.